Faktor-Faktor Yang Menentukan Konsumsi Energi Terbarukan Di Indonesia - Rahmi, Suci; Sri Ulfa Sentosa (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to examine the influence of economic growth, fossil fuel energy consumption, manufacturing value added, total greenhouse gas emissions, and foreign direct investment on renewable energy consumption in Indonesia. This is a quantitative study using secondary data, specifically time series data from the World Bank for the period 1991 to 2021. The analysis method used in this study is multiple linear regression. The results show that all independent variables simultaneously have a significant effect on renewable energy consumption as the dependent variable. Partially, economic growth and fossil fuel energy consumption have a negative but statistically insignificant effect on renewable energy consumption. Manufacturing value added and foreign direct investment have a positive but insignificant effect on renewable energy consumption, while total greenhouse gas emissions have a negative and significant effect on renewable energy consumption. Keywords : Renewable Energy Consumption, Economic Growth, Fossil Fuel Energy Consumption, Manufacturing Value Added, Total Greenhouse Gas Emissions, And Foreign Direct Investment